Tuberculosis contact reminder system in improving tuberculosis screening and retention rate in Perak : an interventional study - Mazalan, Abdulloh Mazalan (2019)
Background: TB screening among contacts remains the cornerstone of successful TB control. Uptake of TB screening among contact in Perak, Malaysia was below required standard. Long duration of TB screening become great challenges to maintain the screening uptake and retention rate among TB contacts. Objectives: The objective of this study was to compare the effectiveness between the newly developed Tuberculosis Contact Reminder System (TCRS) and current system in improving the screening uptake and retention rate in the subsequent screening among TB contacts, staffs’ satisfaction and description of implementation cost. Methodology: An operational research with prospective, parallel and pragmatic design through cluster randomized control trial was conducted in Perak by randomly selected four districts and cluster randomized into group either received TCRS or current system. Data analysis was conducted using SPSS software version 24. Simple and multiple logistic regression analysis were applied to estimate the effectiveness. User satisfaction questionnaire was used to assess the staffs’ satisfaction level and descriptive analysis of cost of implementation. Results: A total of 288 TB contacts were recruited between 12th February and 11th May 2018. Two of the subject in intervention group were excluded due to being transferred to other state and one died of old age which left the intervention group with 141 subjects in the intervention and 144 subjects in the control group. The total screening uptake was significantly higher in intervention compared to control OR 2.48 (95%CI; 1.20, 5.12) and Adj. OR 3.16 (95%CI; 1.26, 7.85) with adjusted baseline characteristic. Higher retention for subsequent TB screening was observed in the intervention group OR 3.74 (95%CI; 2.25, 6.22) and Adj. OR 2.26 (95%CI; 1.18, 4.34) with adjusted baseline. All respondents found the system was useful (100%) and the majority of respondents, 81.8% were satisfied overall. However, half of the respondents agreed that the system was successfully implemented. The cost of reminder system was RM 0.87 and RM 0.57 for first TB screening and subsequent screening respectively. Additional cost RM 1.03 were incurred in case of defaulted contact. Conclusion: The uptake and retention toward TB screening among contacts can be effectively reinforced by TCRS, simultaneously reduced the number of defaulters, increase compliance to screening program and reduce need of defaulter tracing. TCRS may be a new promising system which can be considered in supporting existing contact TB management.